2012
DOI: 10.1186/1471-2164-13-409
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Rdr1 TNL-cluster in roses and other Rosaceous species

Abstract: BackgroundThe resistance of plants to pathogens relies on two lines of defense: a basal defense response and a pathogen-specific system, in which resistance (R) genes induce defense reactions after detection of pathogen-associated molecular patterns (PAMPS). In the specific system, a so-called arms race has developed in which the emergence of new races of a pathogen leads to the diversification of plant resistance genes to counteract the pathogens’ effect. The mechanism of resistance gene diversification has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Determining whether resistance against spot anthracnose is controlled by a single locus or multiple loci has yet to be investigated and is outside of the scope of the present study. In addition, the transgenic rose genotype PC-RGA1, which expresses muRdr1A, one of the nine TNL-NBS-LRR genes in the Rdr1 locus (Terefe-Ayana et al, 2012), was susceptible to all of the isolates used in this study. Recent experiments suggest that muRdr1A is the active gene in race-specific interactions against black spot isolate DortE4 and several other isolates (T. Debener, unpublished data).…”
Section: Discussionmentioning
confidence: 89%
“…Determining whether resistance against spot anthracnose is controlled by a single locus or multiple loci has yet to be investigated and is outside of the scope of the present study. In addition, the transgenic rose genotype PC-RGA1, which expresses muRdr1A, one of the nine TNL-NBS-LRR genes in the Rdr1 locus (Terefe-Ayana et al, 2012), was susceptible to all of the isolates used in this study. Recent experiments suggest that muRdr1A is the active gene in race-specific interactions against black spot isolate DortE4 and several other isolates (T. Debener, unpublished data).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, we used two related rosaceous genomes assuming sufficient microsynteny to the rose genome: the very closely related genome of strawberry and the peach genome, which represents the next-closest relative (Shulaev et al, 2008). In several conventional marker mapping studies, strawberry was shown to be highly similar in its genome structure and marker order with only minor differences to roses (Gar et al, 2011; Spiller et al, 2011; Terefe-Ayana et al, 2012). This strategy proved informative, as we found a couple of clear clusters of significantly associated SNPs in both genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The rose genome displays extensive synteny with the Fragaria vesca genome with only two major rearrangements [9]. Synteny between Fragaria and Rosa genes has been observed for TNL genes (TIR (Drosophila Toll and mammalian interleukin (IL)-1 receptors), NBS (nucleotide-binding site) and LRR (leucine-rich repeat)) [10].…”
Section: Introductionmentioning
confidence: 99%